Pengaruh Model Pembelajaran Problem Base Learning terhadap Kemampuan Berfikir Kritis Siswa pada Pembelajaran Biologi - Annisa Alfira; Rahmadhani Fitri (Lembaga Yasin AlSys, 2023)
Facing the demands of technological developments, there are 4 competencies that must be possessed by students, one of which is the ability to think critically. This study aims to see the influence of the Problem Based Learning learning model from previous research research that has been published so that comparison results related to Problem Base Learning learning outcomes are obtained on students' critical thinking skills at the Senior High School (SMA) level in biology subjects. The method used in this study is a literature study of 5 articles published to Google Schoolar, Mendeley and other scientific publications. The findings of this study show that the Project Base Learning learning model has a positive